STUDI LITERATUR: PENGARUH SMART GENZBOX DALAM PENDEKATAN PEMBELAJARAN MENDALAM UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN KETERLIBATAN MURID PADA MATERI BENUA DAN NEGARA DI DUNIA DI SEKOLAH DASAR - Ikhwatus Syaqiqoh; Eko Handoyo; Sri Sumartiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to comprehensively analyze the effect of Smart Genzbox as an innovative learning media integrated with a deep learning approach in enhancing students’ conceptual understanding and engagement in learning about continents and countries in elementary schools. This research employs a systematic literature review method by examining reputable scientific articles published within the last five years using a thematic synthesis approach. The findings indicate that Smart Box-based media consistently improve conceptual understanding through the presentation of concrete, visual, and interactive learning materials, while also enhancing student engagement across behavioral, emotional, and cognitive dimensions. Furthermore, the integration of a deep learning approach strengthens the knowledge construction process through exploratory activities, conceptual connections, and reflective learning practices. This study identifies a gap in previous literature, which tends to separate the use of learning media from pedagogical approaches and remains predominantly focused on quantitative learning outcomes. Therefore, the novelty of this study lies in the conceptual integration of Smart Genzbox, student engagement, and deep learning within a unified analytical framework. The findings provide both theoretical and practical implications for developing meaningful, interactive, and student-centered learning in elementary education.